Pengaruh Penyemaian yang Berbeda Terhadap Pertumbuhan Tanaman Kelor (Moringa oleifera) - Maulina Novita; Umul Habiyah; Rahmat Hidayat (Journal of Engineering Science and Technology Management (JES-TM), 2022)
Moringa (Moringa oleifera Lam.) is a type of tropical plant that is easy to grow in Indonesia. This plant is starting to be in great demand by the public and one of the types of plants that can be used as potential food. Its high nutritional status and benefits have earned it the nickname Mother's Best friend and Miracle tree. Other benefits of the Moringa plant are as an antimicrobial found in the seeds of the Moringa plant, coagulants in surface water purification efforts (pond water, river water, lake water) and a potential source of biodiesel raw material after jatropha curcas. Moringa cultivation can be done vegetatively and generatively. In this research, we will observe the generative reproduction of Moringa plants, namely through seeds. This study aims to find out how to sow moringa seeds that can produce the best plants. The treatment of soaking seeds in warm water showed a higher percentage of germination compared to immersion in ordinary water. The treatment of soaking the seeds in warm water followed by planting the sprouts in soil media added with manure had a very significant effect on plant height, number of leaves and root length.